Hollow carbon supported metal atom catalyst and preparation method and application thereof

The preparation of hollow carbon-supported metal atomic catalysts through organic acid etching-secondary pyrolysis doping strategy solves the problems of limited loading and insufficient structure in the prior art, and achieves a catalyst with high discharge efficiency and low Tafel slope, suitable for cathode materials for energy storage and conversion batteries.

CN120048927APending Publication Date: 2025-05-27NORTHWESTERN POLYTECHNICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510271753.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-09
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

In the prior art, the loading capacity of the hollow carbon-loaded metal atomic catalyst is limited and its structure is not adjustable enough, resulting in low discharge efficiency and energy efficiency, and the preparation process is complicated and inconvenient to operate, making it difficult to be suitable for industrial production.

Method used

The hollow carbon-supported metal atom catalyst was prepared by organic acid etching-secondary pyrolysis doping strategy, and the ZIF-8 structure was coordinated with the metal ions, and then the hollow structure was formed by etching, and the loading and catalytic activity of the metal atoms were increased by secondary pyrolysis.

Benefits of technology

It realizes a hollow carbon-loaded metal atomic catalyst with high load capacity and adjustable structure, with high discharge efficiency, low Tafel slope and good current stability, and is suitable for cathode materials for energy storage batteries and conversion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120048927A_ABST
    Figure CN120048927A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow carbon supported metal atom catalyst as well as a preparation method and application thereof. The hollow carbon supported metal atom catalyst is formed by supporting one or more metal atoms on a nitrogen-doped carbon polyhedral hollow porous cage-shaped nano structure in an anchoring form. The invention also discloses a preparation method of the hollow carbon supported metal atom catalyst. The hollow carbon supported metal atom catalyst is applied to cathodes of energy storage batteries and conversion batteries. The hollow carbon loaded metal atom catalyst is high in loading capacity, adjustable in structure and high in discharge efficiency and energy efficiency. The method is easy to operate, economical, feasible and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon-supported metal atom catalyst, a preparation method thereof, and an application thereof, and more particularly to a hollow carbon-supported metal atom catalyst, a preparation method thereof, and an application thereof. Background Art

[0002] The functionalized structures and electrochemical properties of single / dual-atom catalysts (SACs / DACs) provide new ideas for improving the energy density, power density, and volume performance of electrochemical energy storage (metal-air batteries, metal-ion batteries, supercapacitors, etc.) and conversion (fuel cell electrocatalysis) devices, and are of great significance for promoting the development of green new energy formats. Currently, loading a high content of metals (such as Fe, Co, Ni, etc.) on a carbon material substrate and functionalizing its structure is crucial for enhancing the oxygen reduction reaction (ORR) rate of electrochemical energy storage and conversion devices.

[0003] The research team of Academician Li Yadong at Tsinghua University (Tian H, et al. Adv. Mater. 2023, 35, 2210714) designed and synthesized carbon vacancy-modified Fe-N-C SACs through microenvironment modulation, achieving efficient utilization of active sites and optimization of electronic structures, and showing high power density and long-term stability of over 1200 hours in rechargeable zinc-air batteries. The research team of Associate Professor Niu Zhiqiang at the Department of Chemical Engineering of Tsinghua University used the in-situ coating and pyrolysis process of MOF to synthesize 10 kinds of dual-atom catalysts containing Fe, Co, Ni, Cu, Mn, and Pd through the macrocyclic precursor-mediated method, and studied the uniqueness of dual-atom sites in the oxygen reduction reaction (Zhang Y X, et al. J. Am. Chem. Soc. 2023, 145, 4819-4827). The research team of Professor Zhang Rufan at Tsinghua University adopted a competitive coordination strategy, using high-concentration zinc ions and high-viscosity polyacrylonitrile in the precursor solution to synergistically inhibit the violent coordination of cobalt ions with 2-methylimidazole, combined with electrospinning and subsequent carbonization processes, to simultaneously achieve atomic-level dispersion of Co and functional catalyst materials of porous nitrogen-doped carbon in series with carbon nanotubes (Han Y, et al. Nano Lett. 2022, 22, 2497-2505). However, the interiors of the above single / dual atoms have a solid structure, resulting in limited active sites and structures that can participate in the reaction.

[0004] In addition to the structural modification of nanoporous materials, hollow carbon spheres have also attracted great attention in both academic and industrial fields due to their encapsulation ability, controllable permeability, surface functionality, high surface-to-volume ratio, excellent chemical and thermal stability, etc. CN116960373A discloses a dual-thin-layer polyphthalocyanine-loaded hollow nanocarbon sphere shell electrocatalyst, its preparation method and application. By using a stepwise self-assembly strategy, metal element catalytic sites with ORR activity and OER activity are uniformly distributed on each side of the hollow nanocarbon sphere shell to balance the competition between the rate-limiting steps of ORR and OER. As the air cathode of a rechargeable zinc-air battery, excellent energy efficiency and cycle stability are achieved. The team of Wang Bo and Wang Lu from Beijing Institute of Technology proposed an acid etching strategy to achieve pore-dependent anisotropic etching of ZIF nanocrystals or even single crystals, and carbonize the ZIF before and after etching. The resulting hollow nitrogen-doped carbon nanomaterials exhibit better catalytic performance in the electrocatalytic oxygen reduction reaction (Chen X C, et al. J. Am. Chem. Soc. 2024, 146, 23138-23145). Although the hollow carbon-supported structure has achieved effective catalytic performance, previous studies usually adopted sacrificial template or confinement strategies. Even though they can effectively inhibit the sintering of metal nanoparticles during high-temperature treatment, the related methods are cumbersome to operate, and the metal atom loading of the prepared materials can only be increased limitedly.

[0005] CN111924820A discloses a preparation method of a hollow-structured metal single-atom site carbon composite material, which is to disperse a metal-organic framework material prepared with a doped metal salt into a protonic solvent, perform etching and high-temperature pyrolysis to obtain the hollow-structured metal single-atom site carbon composite material. However, the selection range of protonic solvents is limited, and the requirements for the prepared materials are relatively high.

[0006] CN107459029A discloses a nitrogen / metal atom-doped hollow polyhedral nanocarbon shell material and its preparation method. The organic metal framework raw material is prepared by a low-temperature hydrothermal method / solvothermal method, and then through high-temperature carbonization combined with ultrasonic exfoliation and centrifugal separation and other means, the nitrogen / metal atom-doped hollow polyhedral nanocarbon shell material is obtained. However, the preparation process requires strict control of low-temperature conditions.

[0007] CN115558942A discloses an oxygen-doped carbon hollow sphere anchored with metal palladium single atoms, its preparation method and application. Similar to the preparation process of CN107459029A, the oxygen-doped carbon hollow sphere anchored with metal palladium single atoms is obtained through steps such as low-temperature hydrothermal treatment, high-temperature carbonization, acid etching and centrifugal separation. It also has relatively high requirements for temperature, a limited variety of acids, and a single metal loading type and limited loading amount.

[0008] Therefore, there is an urgent need to develop a hollow carbon-supported metal atom catalyst with a high loading capacity, adjustable structure, high discharge efficiency and energy efficiency, simple operation, economic feasibility, and suitability for industrial production, as well as its preparation method and application. Summary of the Invention

[0009] The technical problem to be solved by the present invention is to overcome the above-mentioned defects existing in the prior art and provide a hollow carbon-supported metal atom catalyst with a high loading capacity, adjustable structure, high discharge efficiency and energy efficiency, as well as its application.

[0010] The further technical problem to be solved by the present invention is to overcome the above-mentioned defects existing in the prior art and provide a preparation method for a hollow carbon-supported metal atom catalyst with simple operation, economic feasibility, and suitability for industrial production.

[0011] The technical solution adopted by the present invention to solve its technical problems is as follows: A hollow carbon-supported metal atom catalyst is formed by anchoring one or several metal atoms on a nitrogen-doped carbon polyhedron hollow porous cage-like nanostructure. The hollow carbon-supported metal atom catalyst of the present invention has a typical hollow carbon nanocage structure, which can serve as a nano-reactor, improving the exposure and accessibility of active sites; the hollow carbon nanocage structure can also prevent toxic substances from entering the active center, thereby preventing catalyst poisoning. Due to its unique hollow design, the catalyst with a hollow structure of the present invention has a larger specific surface area compared with a solid structure, which means that more active sites can be exposed on the catalyst surface, thus improving the catalytic efficiency; while the metal anchored on the hollow structure can reduce the migration and aggregation of metal atoms, improving the stability and durability of the catalyst, which is crucial for maintaining the long-term efficient operation of the catalyst. The polyhedron includes six-sided, eight-sided, or twelve-sided, etc.

[0012] Preferably, the particle size of the hollow carbon-supported metal atom catalyst is 360 - 700 nm (more preferably 500 - 680 nm), and the carbon shell thickness is 18 - 100 nm (more preferably 50 - 98 nm). The particle size and carbon shell thickness directly affect its thermal stability. A smaller particle size exposes more active sites, and changes in the carbon shell thickness may change the coordination environment of metal atoms; by controlling the particle size and carbon shell thickness, the performance of the single-atom catalyst can be optimized to meet specific catalytic requirements.

[0013] Preferably, the specific surface area of the hollow carbon-supported metal atom catalyst is 1000 - 1400 m 2 ·g -1 , and the specific surface area inside the mesopores is 0.1 - 0.4 cm 3 ·g -1 ·nm -1 (more preferably 0.25 - 0.35 cm 3 ·g -1·nm -1 ). A large specific surface area means that more active sites of the single-atom catalyst are exposed, which is beneficial to increasing the contact area of the catalytic reaction and making the active sites evenly distributed, thereby enhancing the adsorption capacity of the catalyst for reactants and improving the selectivity and efficiency of the catalytic reaction.

[0014] Preferably, in the hollow carbon-supported metal atom catalyst, the total loading amount of metal atoms is 0.5-25 wt% (more preferably 0.5-10 wt%, even more preferably 0.5-5 wt%), and the mass fraction of nitrogen doping is 5-10 wt%. A high loading amount of metal atoms is loaded on the carbon support to form active centers with a high surface density, maximizing the catalytic efficiency and stability of the metal atom catalyst.

[0015] Preferably, the metal atoms include one or more of iron, nickel, cobalt, tin, manganese, copper, cerium, molybdenum, vanadium, ruthenium, etc. Different combinations of metal atoms can improve and optimize the catalytic activity and stability.

[0016] The technical solution adopted by the present invention to further solve its technical problems is as follows: A preparation method of a hollow carbon-supported metal atom catalyst, comprising the following steps: (1) Rapidly add an alcohol solution of an imidazole-based organic ligand to an alcohol solution containing a zinc salt and other metal salts, stir and react, then centrifuge, wash the precipitate, and freeze-dry to obtain metal-ZIF-8 powder; (2) Disperse the metal-ZIF-8 powder obtained in step (1) in an organic acid solution, etch it, then centrifuge, wash the precipitate, centrifuge, and vacuum-dry to obtain a brownish-beige hollow powder; (3) Carbonize the brownish-beige hollow powder obtained in step (2) under an inert atmosphere, and then cool to room temperature to obtain a black hollow carbon powder; (4) Disperse the black hollow carbon powder obtained in step (3) in water, add an alcohol solution containing the same other metal salts as in step (1) again, stir and react, then centrifuge, freeze-dry, perform heat treatment under an inert atmosphere, and cool to room temperature to obtain a hollow carbon-supported metal atom catalyst.

[0017] The inventive concept of the method of the present invention is as follows: The method of the present invention prepares a catalyst with a high loading of metal atoms anchored on hollow nitrogen-doped carbon through an organic acid etching-secondary pyrolysis doping strategy. In the mixed solution, zinc ions coordinate with imidazole-based organic ligands to form the crystal structure of ZIF-8. Meanwhile, in this process, metal ions are fixed in the framework of ZIF-8 by means of coordination chemistry; in step (2), organic acid etching can form a hollow carbon nanocage structure in the catalyst. This structure can provide more active sites and a larger specific surface area, which is conducive to the diffusion of reactants and products, thereby accelerating the reaction rate. Moreover, organic acid etching can enhance the interaction between metal nanoparticles and the carrier, form defects on the catalyst surface, making them serve as active sites and enhancing the redox ability of the catalyst; in addition, organic acid etching can also adjust the chemical bond length in the metal-organic framework catalyst, optimize the electronic structure and reaction kinetics of the catalyst; secondary pyrolysis doping increases the physical and chemical adsorption of metal atoms on the catalyst surface, and then increases the metal atom loading rate on the catalyst surface, thereby optimizing the electronic properties and catalytic activity of the catalyst.

[0018] Preferably, in step (1), the volume ratio of the alcohol solution of the imidazole-based organic ligand to the alcohol solution containing zinc salt and other metal salts is 1:6 to 12 (more preferably 1:7 to 11). Under the dosage of the zinc salt, it is beneficial to control the morphology and size of ZIF-8 crystals, and has an excellent pore structure, providing more active sites for the loading of other metal atoms, and can also control the distribution of metal nodes, thereby obtaining ZIF-8 with a good distribution of metal atoms; under the dosage of other metals, other metal salts can form alloys with zinc, changing the electronic structure and surface properties of the catalyst, thereby improving its catalytic activity and selectivity.

[0019] Preferably, in step (1), the concentration of N element in the alcohol solution of the imidazole-based organic ligand is 1 to 10 mol / L (more preferably 1.2 to 6.0 mol / L). The concentration of the imidazole-based organic ligand, especially the concentration of N contained therein, directly affects the nucleation and growth rates of ZIF-8 crystals, changes the pore size distribution and porosity of ZIF-8, controls the specific surface area of the final catalyst, and obtains a well-structured ZIF-8 structure, providing support for promoting the mass transfer efficiency and reaction kinetics of the catalyst and improving the catalytic activity and selectivity of the catalyst.

[0020] Preferably, in step (1), the rapid addition means adding within 1 to 3 minutes.

[0021] Preferably, in step (1), in the alcohol solution containing zinc salt and other metal salts, the concentration of zinc ions in the zinc salt is 3 to 100 mmol / L (more preferably 10 to 70 mmol / L), and the molar ratio of metal ions in other metal salts to zinc ions in the zinc salt is 0.005 to 0.4:1 (more preferably 0.008 to 0.2:1). When the metal atom is a single / double atom, the molar ratio of metal ions in one or two other metal salts to zinc ions in the zinc salt is 0 to 0.2:0.005 to 0.2:1 (when the metal atom is a double atom, more preferably 0.008 to 0.1:0.008 to 0.1:1). The alcohol solution ratio of the metal salts affects the dispersion and uniformity of metal atoms on the support. At the above concentrations, the reaction rate between reactants can reach the optimum, which is beneficial to the nucleation and growth process of the catalyst precursor, controls the morphology and size of the product, so as to obtain a metal-organic framework with good structure, that is, the zeolitic imidazolate framework ZIF structure. At the same time, a high metal dispersion can be achieved, avoiding the aggregation of metal atoms to form large nanoparticles, and realizing the uniform dispersion of other metals on the ZIF structure, thereby improving the activity and selectivity of the catalyst.

[0022] Preferably, in step (1), the stirring reaction means: in a water bath at room temperature to 50 °C (more preferably 30 to 45 °C), at a rotation speed of 800 to 1400 r / min (more preferably 1000 to 1300 r / min), stir for 10 to 60 h (more preferably 12 to 36 h). During the stirring reaction, a coordination bond is formed between metal ions and nitrogen atoms on the imidazole ring. With the continuation of stirring, these coordination complexes will further polymerize to form larger ZIF-8 structures, which have highly ordered pores.

[0023] Preferably, in step (1), wash with methanol and / or ethanol, or their aqueous solutions 2 to 15 times (more preferably 4 to 10 times). The sufficient washing of the alcohol solution is to remove the excess unreacted zinc salt or imidazole-based organic ligand in the above synthesis process, as well as impurities that may be introduced during the synthesis process, such as solvent residues, reaction by-products, etc., to obtain a purer complex, thereby improving the performance of the catalyst.

[0024] Preferably, in step (1), the freeze-drying temperature is -30 to -55 °C, the vacuum degree is 10 to 30 Pa, and the time is 12 to 60 h (more preferably 18 to 48 h). Freeze-drying can maintain the original structural morphology of the material, making the ZIF-derived carbon support have a super high specific surface area and a large pore structure, which helps to fully expose the metal active sites and improve the dispersion of metal particles on the carbon support. The vacuum degree of the freeze-drying is the absolute pressure.

[0025] Preferably, in step (1), the method for preparing the alcoholic solution of the imidazole-based organic ligand is as follows: adding the imidazole-based organic ligand into the alcoholic solution and stirring until dissolved.

[0026] Preferably, in step (1), the imidazole-based organic ligand includes one or more of imidazole, 2-methylimidazole, 2-nitroimidazole, etc.

[0027] Preferably, in step (1), the method for preparing the alcoholic solution of the zinc salt and other metal salts is as follows: adding the zinc salt and other metal salts into the alcoholic solution and stirring until dissolved.

[0028] Preferably, in step (1), the zinc salt includes Zn(NO 3 ) 2 ·6H 2 O, etc.

[0029] Preferably, in step (1), the other metal salts include one or more of iron salts, nickel salts, cobalt salts, tin salts, manganese salts, copper salts, cerium salts, molybdenum salts, vanadium salts, ruthenium salts, and their hydrates, etc. More preferably, the other metal salts include iron acetate, Fe(NO 3 ) 3 ·9H 2 O, FeCl 3 ·6H 2 O, Ni(NO 3 ) 2 ·6H 2 O, Co(NO 3 ) 2 ·6H 2 O, SnCl 2 ∙2H 2 O, Mn(NO 3 ) 2 ·4H 2 O, Cu(NO 3 ) 2 ·3H 2 O, Ce(SO 4 ) 2 ·2H 2 O, Ce(NO 3 ) 3 ·3H 2 O, Na 2 MoO 4 ·2H 2 O, V 2 O 5 ·5H 2 O or RuCl 3 ·3H 2 O, etc.

[0030] Preferably, in step (1), the alcohol solutions are all methanol and / or ethanol, or their aqueous solutions.

[0031] Preferably, the temperature for stirring and dissolving is room temperature to 50 °C (more preferably 30 to 45 °C), and the time is 20 to 60 min (more preferably 20 to 40 min).

[0032] Preferably, in step (2), the mass-volume ratio of the metal-ZIF-8 powder to the organic acid solution is 5 to 100 g / L (more preferably 10 to 80 g / L). The pH value and volume of the organic acid solution determine the etching degree of the ZIF-8 powder. At the said ratio, it can ensure that the internal structure of ZIF-8 is effectively etched to form a hollow structure without causing the complete dissolution of the metal-ZIF-8 powder, thus retaining the required structural features.

[0033] Preferably, in step (2), the etching temperature is room temperature to 60 °C (more preferably 30 to 55 °C), and the time is 3 to 72 h (more preferably 3 to 48 h, even more preferably 3 to 24 h). The etching temperature affects the pore structure and specific surface area of the ZIF-8 crystal. Within a certain temperature range, a higher etching temperature helps to expand the pores and increase the specific surface area of the material, thus providing more active sites for the single-atom catalyst. The length of the etching time directly affects the formation degree and integrity of the hollow structure. If the etching time is insufficient, it may be difficult to completely form the hollow structure or the structure is not uniform enough; while if the etching time is too long, it may lead to over-corrosion of the structure, destroying the stability and active sites of the catalyst. At the said etching temperature and time, the etching rate can be well regulated, and the etching process can be adjusted from inside to outside or from outside to inside to achieve fine regulation of the ZIF structure. The obtained hollow structure after etching can protect the metal nanoparticles anchored on the carbon surface inside and can also avoid sintering and aggregation under subsequent high-temperature reaction conditions, improving the thermal stability of the catalyst.

[0034] Preferably, in step (2), the pH value of the organic acid solution is 2.0 to 3.5. A lower pH value usually means a higher acid concentration, which can accelerate the etching rate, adjust the etching from inside to outside, and achieve precise regulation of the hollow structure. At the said pH value, it is more conducive to creating abundant defect sites on the surface of the metal or alloy by the organic acid. These defect sites are used to stabilize and capture single atoms, enhancing the stability and activity of the catalyst.

[0035] Preferably, in step (2), the organic acid solution includes one or more of tannic acid, formic acid, acetic acid, propionic acid, butyric acid, difluoroacetic acid, trifluoroacetic acid, isobutyric acid, or 2-methylbutyric acid, etc.

[0036] Preferably, in step (2), it is washed 3 to 12 times (more preferably 4 to 10 times) with methanol and / or ethanol, or their aqueous solutions. Through sufficient washing, the unreacted precursors, residual solvents or other organic impurities on the solid precipitate are completely removed.

[0037] Preferably, in step (2), the temperature of the vacuum drying is 60 to 100 °C, the vacuum degree is -0.01 to -0.10 MPa, and the time is 4 to 36 h (more preferably 6 to 24 h). The vacuum degree of the vacuum drying is the relative pressure.

[0038] Preferably, in step (3), the carbonization treatment means: heating to 600 to 1500 °C (more preferably 1000 to 1400 °C) at a rate of 1 to 40 °C / min (more preferably 5 to 35 °C / min), and carbonization treatment for 1 to 24 h (more preferably 2 to 12 h, even more preferably 2 to 8 h). A slower heating rate helps the uniform pyrolysis of the precursor, can well control the pyrolysis rate of the material, decompose the N-containing organic ligand in ZIF, in-situ generate N-doped C polyhedra, Zn will volatilize, thus generating a large number of micropores, and at the same time avoid the thermal stress and the destruction of the material structure caused by rapid heating, enabling the material to fully react at high temperature to form the desired phase and structure. Sufficient heat preservation time can ensure that the material fully reacts and rearranges at high temperature.

[0039] Preferably, in step (3), it is cooled to room temperature at a rate of 1 to 30 °C / min (more preferably 5 to 25 °C / min). The cooling rate affects the crystallinity and phase composition of the material. Rapid cooling may produce non-equilibrium phases and defects, while slow cooling enables the material to be evenly cooled to room temperature, avoiding thermal stress and contributing to the formation of a thermodynamically stable phase.

[0040] Preferably, in step (4), the concentration of the hollow carbon powder dispersed in water is 20 to 30 mg / mL.

[0041] Preferably, in step (4), the volume ratio of water to the alcohol solution is 1:1 to 3 (more preferably 1:1 to 2).

[0042] Preferably, in step (4), in the alcohol solution, the total concentration of metal ions is 0.2 to 8.0 mmol / L (more preferably 0.2 to 4.0 mmol / L). The concentration or ratio of metal ions will affect the alloy structure and degree formed during the chemical reduction and subsequent heat treatment of the catalyst, resulting in changes in the electronic structure of the active sites in the catalyst. The concentration can optimize the physical and chemical state of the active sites, form a highly dispersed metal atom structure catalyst, have more surface Brønsted acid sites, enhance the stability of the catalyst, and thus affect the catalytic activity of the catalyst.

[0043] Preferably, in step (4), the temperature of the stirring reaction is from room temperature to 50 °C (more preferably 30 - 40 °C), the rotation speed is 500 - 1200 r / min (more preferably 800 - 1200 r / min), and the stirring time is 3 - 24 h (more preferably 6 - 18 h). During the secondary doping process, stirring helps the uniform distribution of the metal hollow carbon powder in the reaction system, ensuring the uniformity of doping. At the said temperature and rotation speed, the oversaturation of the metal hollow carbon powder in local areas can be avoided, thereby reducing the agglomeration phenomenon and forming uniformly dispersed atomic active sites, maintaining the high specific surface area and high active site density of the catalyst.

[0044] Preferably, in step (4), the freeze-drying temperature is -30 to -55 °C, the vacuum degree is 10 - 30 Pa, and the time is 6 - 72 h (more preferably 12 - 48 h). Freeze-drying can maintain the original structural morphology of the material, enabling the ZIF-derived carbon carrier to have an ultra-high specific surface area and a large pore structure, which helps to fully expose the metal active sites and improve the dispersion of metal particles on the carbon carrier during the secondary doping process. The vacuum degree of the freeze-drying is the absolute pressure.

[0045] Preferably, in step (4), the heat treatment means: heating to 800 - 1600 °C (more preferably 1000 - 1400 °C) at a rate of 1 - 50 °C / min (more preferably 5 - 30 °C / min), and heat-treating for 2 - 6 h (more preferably 3 - 5 h). The secondary heat treatment can control the dispersion state of metal atoms on the carrier by precisely controlling the temperature and time of the heat treatment, prevent their aggregation to form clusters or nanoparticles at high temperatures, and can change the electronic properties of metal atoms, enhancing the interaction between metal atoms and the carrier, thereby increasing the loading amount of metal atoms, the thermal stability of the catalyst, and the dispersion of active sites.

[0046] Preferably, in step (4), it is cooled to room temperature at a rate of 1 - 30 °C / min (more preferably 5 - 25 °C / min). Cooling at the said rate can reduce the migration and aggregation of metal particles, helping to maintain the dispersion of metal particles, thereby improving the thermal stability and activity of the catalyst.

[0047] Preferably, in steps (3) and (4), the inert atmosphere includes one or more of nitrogen, argon, helium, etc. The inert atmospheres used in the present invention are all high-purity atmospheres with a purity ≥ 99.999%.

[0048] The technical solution adopted by the present invention to further solve its technical problems is as follows: an application of a hollow carbon-loaded metal atom catalyst, wherein the hollow carbon-loaded metal atom catalyst is applied to the cathode of an energy storage battery and a conversion battery; the energy storage battery includes a metal-air battery, a metal ion battery or a supercapacitor, etc.; the conversion battery includes a microbial fuel cell, etc. The specific method is as follows: the hollow carbon-loaded metal atom catalyst and acetylene black or Pt / C are mixed in a mass ratio of 6 to 9:1, placed in a mortar, 10 to 15 mg of acetylene black or Pt / C: 1 mL of ethanol solution are added dropwise with an ethanol solution for grinding to form a mixed slurry, and then a 60% polytetrafluoroethylene emulsion equivalent to 3 to 6% of the volume of the ethanol solution is added dropwise with a pipette to the mixed slurry, and then 10 to 15 mg of acetylene black: 1 mL of ethanol solution is added dropwise with an ethanol solution, and the mixture is fully ground to obtain a sheet-like catalytic layer; the nickel foam, the water-proof and breathable membrane, and the sheet-like catalytic layer are fixed in order, and the three are pressed together on a roller press to obtain a cathode for energy storage batteries and green power generation devices.

[0049] The beneficial effects of the present invention are as follows: (1) The hollow carbon-supported metal atom catalyst of the present invention has a high loading capacity, an adjustable structure, high discharge efficiency and energy efficiency, and a half-wave potential (E 1 / 2 ) up to 0.922 V (vs RHE), Tafel slope as low as 52mV·dec -1 , charge transfer resistance as low as 93Ω, capacitance as high as 77.2mF·cm -2 , after running for 8 hours, the current stability is still maintained at 95.8%; (2) The present invention provides a new solution for improving the catalytic activity and stability of metal atoms and preparing a series of hollow carbon-supported metal atom catalysts. The invention can be applied to energy storage battery systems such as metal-air batteries, metal ion batteries, supercapacitors, and power generation systems of conversion batteries such as microbial fuel cells, which can make them have higher energy efficiency and better energy conservation and emission reduction advantages. At the same time, it provides new insights for expanding and deepening the research in the field of hollow carbon-based atomic structure electrocatalysts, and promotes and accelerates the practical application and industrialization of the preparation technology of hollow carbon-supported metal atom catalysts. (3) The method of the present invention is simple to operate, economically feasible, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is a SEM image of Example 1 of the hollow carbon supported Fe atom catalyst Fe SA / NhC of the present invention; Figure 2 is a TEM image of Example 1 of the hollow carbon supported Fe atom catalyst Fe SA / NhC of the present invention; Figure 3It is the aberration-corrected electron microscopy image of Example 1 of the Fe SA / NhC catalyst with hollow carbon-supported Fe atoms of the present invention; Figure 4 It is the BET graph of Example 5 of the FeMn DA / NhC catalyst with hollow carbon-supported Fe and Mn atoms and Comparative Example 3 of the FeMn DA / NC catalyst with solid carbon-supported Fe and Mn atoms of the present invention; Figure 5 It is the pore size distribution graph of Example 5 of the FeMn DA / NhC catalyst with hollow carbon-supported Fe and Mn atoms and Comparative Example 3 of the FeMn DA / NC catalyst with solid carbon-supported Fe and Mn atoms of the present invention; Figure 6 It is the Nyquist impedance graph of Example 1 of the Fe SA / NhC catalyst with hollow carbon-supported Fe atoms, Example 2 of the Mn SA / NhC catalyst with hollow carbon-supported Mn atoms, Example 5 of the FeMn DA / NhC catalyst with hollow carbon-supported Fe and Mn atoms, Comparative Example 1 of the Fe SA / NC catalyst with solid carbon-supported Fe atoms, Comparative Example 2 of the Mn SA / NC catalyst with solid carbon-supported Mn atoms, and Comparative Example 3 of the FeMn DA / NC catalyst with solid carbon-supported Fe and Mn atoms of the present invention; Figure 7 It is a graph of capacitance and current measured at 1.10 V plotted as a function of scan rate for Example 1 of the Fe SA / NhC catalyst with hollow carbon-supported Fe atoms, Example 2 of the Mn SA / NhC catalyst with hollow carbon-supported Mn atoms, Example 5 of the FeMn DA / NhC catalyst with hollow carbon-supported Fe and Mn atoms, Comparative Example 1 of the Fe SA / NC catalyst with solid carbon-supported Fe atoms, Comparative Example 2 of the Mn SA / NC catalyst with solid carbon-supported Mn atoms, and Comparative Example 3 of the FeMn DA / NC catalyst with solid carbon-supported Fe and Mn atoms of the present invention; Figure 8 It is the ORR LSV curve graph of Example 1 of the Fe SA / NhC catalyst with hollow carbon-supported Fe atoms, Example 2 of the Mn SA / NhC catalyst with hollow carbon-supported Mn atoms, Example 5 of the FeMn DA / NhC catalyst with hollow carbon-supported Fe and Mn atoms, Comparative Example 1 of the Fe SA / NC catalyst with solid carbon-supported Fe atoms, Comparative Example 2 of the Mn SA / NC catalyst with solid carbon-supported Mn atoms, and Comparative Example 3 of the FeMn DA / NC catalyst with solid carbon-supported Fe and Mn atoms of the present invention; Figure 9It is the Tafel slope diagram of Example 1 of the Fe SA / NhC hollow carbon-supported Fe atom catalyst of the present invention, Example 2 of the Mn SA / NhC hollow carbon-supported Mn atom catalyst, Example 5 of the FeMn DA / NhC hollow carbon-supported Fe and Mn atom catalyst, Comparative Example 1 of the Fe SA / NC solid carbon-supported Fe atom catalyst, Comparative Example 2 of the Mn SA / NC solid carbon-supported Mn atom catalyst, and Comparative Example 3 of the FeMn DA / NC solid carbon-supported Fe and Mn atom catalyst; Figure 10 It is the current-time curve of Example 5 of the FeMn DA / NhC hollow carbon-supported Fe and Mn atom catalyst of the present invention and Pt / C; Figure 11 It is the SEM diagram of Example 4 of the FeCo DA / NhC hollow carbon-supported Fe and Co atom catalyst of the present invention; Figure 12 It is the TEM diagram of the Fe SA / NC solid carbon obtained in Comparative Example 1 of the present invention; In the figure, SA and DA are the abbreviations of single-atom catalyst Single-atom and dual-atom catalyst Daul-atom respectively; NC and NhC are the abbreviations of nitrogen-doped carbon N-doped Carbon and nitrogen-doped hollow carbon N-doped Hollow Carbon respectively. Detailed implementation mode

[0051] The present invention will be further described below in conjunction with examples and drawings.

[0052] The Pt / C and acetylene black catalysts used in the examples and comparative examples of the present invention were purchased from Shanghai Hesen Electric Co., Ltd.; the purity of the high-purity atmosphere used in the examples and comparative examples of the present invention is ≥99.999%; the raw materials or chemical reagents used in the examples of the present invention are obtained through conventional commercial channels without special instructions.

[0053] Example 1 of a hollow carbon-supported Fe atom catalyst The hollow carbon-supported Fe atom catalyst is formed by anchoring Fe atoms on a nitrogen-doped carbon dodecahedron hollow porous cage-like nanostructure; the particle size of the hollow carbon-supported Fe atom catalyst is 603.66±26.42 nm, and the carbon shell thickness is 92.4±5.6 nm; the specific surface area of the hollow carbon-supported metal atom catalyst is 1175.4 m 2 ·g -1 , and the specific surface area inside the mesopores is 0.233 cm 3 ·g -1 ·nm -1; In the hollow carbon-supported Fe atom catalyst, the loading amount of Fe atoms is 0.54 wt%, and the mass fraction of nitrogen doping is 6.8 wt%.

[0054] As Figure 1 , 2 shown, the hollow carbon-supported Fe atom catalyst Fe SA / NhC in the embodiment of the present invention is a dodecahedral hollow porous cage-like nanostructure. The catalyst is uniformly dispersed, with a particle size of 603.66 ± 26.42 nm. The cross-section has a hollow structure, and the carbon shell thickness is 92.4 ± 5.6 nm.

[0055] As Figure 3 shown, the metal particles on the surface of the hollow carbon-supported Fe atom catalyst Fe SA / NhC in the embodiment of the present invention are uniformly dispersed and loaded in an anchored form, without agglomeration.

[0056] After testing, the specific surface area of the hollow carbon-supported Fe atom catalyst Fe SA / NhC in the embodiment of the present invention is 1175.4 m 2 ·g -1 , far exceeding the specific surface area of 531.7 m 2 ·g -1 of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in Comparative Example 1, indicating that due to its unique structure, the hollow carbon material has a larger specific surface area, and thus more active sites can be used to participate in the catalytic reaction.

[0057] After testing, the specific surface area of the mesopores in the hollow carbon-supported Fe atom catalyst Fe SA / NhC in the embodiment of the present invention is 0.233 cm 3 ·g -1 ·nm -1 , which is 0.25 times more than that in Comparative Example 1, indicating that the hollow structure of the hollow carbon material helps to reduce the weight while maintaining a large specific surface area.

[0058] After testing, in the hollow carbon-supported Fe atom catalyst Fe SA / NhC in the embodiment of the present invention, the loading amount of Fe atoms is 0.54 wt%, and the mass fraction of nitrogen doping is 6.8 wt%.

[0059] Example 1 of the preparation method of a hollow carbon-supported Fe atom catalyst (1) Rapidly add 30 mL of a methanol solution of 1.622 mol / L 2-methylimidazole to 270 mL containing 50.42 mmol / L Zn(NO 3 ) 2 ·6H 2 O and 0.495 mmol / L Fe(NO 3 ) 3 ·9H2 In a methanol solution of O, at a water bath temperature of 35 °C and a rotation speed of 1000 r / min, after stirring and reacting for 12 h, centrifugation is carried out for solid-liquid separation. The white precipitate is collected, and the white precipitate is washed 6 times with a methanol solution. Then, it is freeze-dried at -30 °C and a vacuum degree of 20 Pa for 24 h to obtain Fe-ZIF-8 powder; The preparation method of the methanol solution of the imidazole is as follows: Add 4.0 g (0.0487 mol) of 2-methylimidazole into 30 mL of methanol solution, and stir and dissolve it at 35 °C for 30 min to obtain it; the said Zn(NO 3 ) 2 ·6H 2 O and Fe(NO 3 ) 3 ·9H 2 O methanol solution preparation method is: Add 4.05 g (0.0136 mol) of Zn(NO 3 ) 2 ·6H 2 O and 54 mg (0.134 mmol) of Fe(NO 3 ) 3 ·9H 2 O into 270 mL of methanol solution, and stir and dissolve it at 35 °C for 30 min to obtain it; (2) Disperse 0.5 g of the Fe-ZIF-8 powder obtained in step (1) into 50 mL of tannic acid solution with a pH value of 3.0, and carry out etching at 45 °C for 3 h. Then, centrifugation is carried out for solid-liquid separation. The precipitate is collected, and the precipitate is washed 6 times with a methanol solution. Centrifugation is carried out again to collect the precipitate, which is placed in a vacuum drying oven and vacuum-dried at 70 °C and -0.08 MPa for 8 h to obtain a brownish-beige hollow powder; (3) Place the brownish-beige hollow powder obtained in step (2) into a tubular furnace. Under a high-purity nitrogen atmosphere, heat it to 1200 °C at a rate of 5 °C / min, carry out carbonization treatment for 3 h, and then cool it to room temperature at a rate of 10 °C / min to obtain black hollow carbon powder; (4) Disperse 500 mg of the black hollow carbon powder obtained in step (3) into 20 mL, and then add 30 mL of 0.495 mmol / L Fe(NO 3 ) 3 ·9H 2A methanol solution of O was stirred and reacted for 12 h in a 35 °C water bath at a rotation speed of 1000 r / min, followed by centrifugation for solid-liquid separation. It was freeze-dried for 24 h at -30 °C and a vacuum degree of 20 Pa. Then, the obtained powder was placed in a tubular furnace and heated to 1000 °C at a rate of 10 °C / min in a high-purity nitrogen atmosphere for heat treatment for 4 h, and then cooled to room temperature at a rate of 10 °C / min to obtain a hollow carbon-supported Fe atom catalyst Fe SA / NhC.

[0060] Application Example 1 of a Hollow Carbon-Supported Fe Atom Catalyst The hollow carbon-supported Fe atom catalyst FeSA / NhC obtained in the example of the method of the present invention was applied to the air cathode of a zinc-air battery. The specific method was as follows: 90 mg of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in the example of the method of the present invention and 10 mg of acetylene black were mixed and placed in a mortar. 1 mL of ethanol was added dropwise to the mortar for grinding to form a mixed slurry. Then, 40 μL of a 60% polytetrafluoroethylene emulsion was added dropwise to the mixed slurry with a pipette, and then 1 mL of an ethanol solution was added, followed by sufficient grinding to obtain a flaky catalytic layer. It was fixed in the order of nickel foam, a water-repellent and air-permeable membrane, and the flaky catalytic layer, and the three were pressed into one body on a roll press to obtain an air cathode.

[0061] To evaluate the electrochemical performance of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in the example of the method of the present invention, it was first prepared into a catalyst ink. The specific method was as follows: 6 mg of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in the example of the method of the present invention and 40 μL of a Nafion solution were dispersed in 960 μL of a water / isopropanol (volume ratio 3:1) mixture to prepare a catalyst ink.

[0062] ORR test method: 20 μL of the catalyst ink was deposited on a glassy carbon electrode with a diameter of 5 mm and dried at room temperature for 30 min. An ORR test was carried out using a three-electrode electrochemical device (CHI 660E workstation). LSV curve test method: A graphite rod was used as the counter electrode, and a saturated Ag / AgCl in a potassium chloride solution was used as the reference electrode. According to the Nernst equation, all recorded potentials were converted to the ratio of potential to RHE. The electrocatalytic LSV curve of the catalyst was recorded in an oxygen atmosphere saturated with 0.1 mol / L KOH, with a scanning rate of 5 mV / s and a rotation speed of 400 - 1600 rpm.

[0063] As Figure 6 、 7 shown, the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in the example of the method of the present invention has a low charge transfer resistance of 128 Ω and a capacitance of 58.3 mF·cm -2。

[0064] As Figure 8 、 9 shown, the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in the method embodiment of the present invention is 0.899 V (vs. RHE), and the Tafel slope is relatively low, being 56 mV·dec -1 . Both are far superior to the corresponding electrochemical properties of the solid carbon structure Fe SA / NC obtained in Comparative Example 1, and have high ORR activity, indicating that the hollow structure can provide more specific surface area and active sites for metal atoms, and can significantly improve the ORR catalytic activity of the catalyst.

[0065] After detection, the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in the method embodiment of the present invention has high current stability. After running for 8 h, it still has a current retention rate of 94.7%, which is superior to the current retention rate of 88.9% of the commercial Pt / C catalyst.

[0066] Example 2 of a hollow carbon-supported Mn atom catalyst The hollow carbon-supported Mn atom catalyst is formed by anchoring Mn atoms on a nitrogen-doped carbon dodecahedron hollow porous cage-like nanostructure; the particle size of the hollow carbon-supported Mn atom catalyst is 635.32 ± 32.67 nm, and the carbon shell thickness is 89.3 ± 5.8 nm; the specific surface area of the hollow carbon-supported Mn atom catalyst is 1150.2 m 2 ·g -1 , and the specific surface area inside the mesopores is 0.245 cm 3 ·g -1 ·nm -1 ; in the hollow carbon-supported Mn atom catalyst, the loading amount of Mn atoms is 0.51 wt%, and the mass fraction of nitrogen doping is 6.5 wt%.

[0067] After detection, the hollow carbon-supported Mn atom catalyst Mn SA / NhC in the embodiment of the present invention is a dodecahedron hollow porous cage-like nanostructure. The catalyst is uniformly dispersed, the particle size is 635.32 ± 32.67 nm, the cross-section has a hollow structure, and the carbon shell thickness is 89.3 ± 5.8 nm.

[0068] After detection, the metal particles on the surface of the hollow carbon-supported Mn atom catalyst Mn SA / NhC in the embodiment of the present invention are uniformly dispersed and anchored, without agglomeration.

[0069] After detection, the specific surface area of the hollow carbon-supported Mn atom catalyst Mn SA / NhC in the embodiment of the present invention is 1150.2 m 2 ·g -1, far exceeding the specific surface area of 517.3 m of the solid carbon-supported Mn atomic catalyst Mn SA / NC obtained in Comparative Example 2 2 ·g -1 , indicating that due to its unique structure, the hollow carbon material has a larger specific surface area, and thus more active sites can be used to participate in the catalytic reaction.

[0070] After testing, the specific surface area inside the mesopores of the hollow carbon-supported Mn atomic catalyst Mn SA / NhC in the embodiment of the present invention is 0.245 cm 3 ·g -1 ·nm -1 , which is 0.39 times more than that in Comparative Example 2, indicating that the hollow structure of the hollow carbon material helps to reduce the weight while maintaining a large specific surface area.

[0071] After testing, in the hollow carbon-supported Mn atomic catalyst Mn SA / NhC in the embodiment of the present invention, the loading amount of Mn atoms is 0.51 wt%, and the mass fraction of nitrogen doping is 6.5 wt%.

[0072] Example 2 of the preparation method of a hollow carbon-supported Mn atomic catalyst (1) Rapidly add 30 mL of a methanol solution of 2-methylimidazole at 1.136 mol / L to 270 mL of a methanol solution containing 37.35 mmol / L Zn(NO 3 ) 2 ·6H 2 O and 0.797 mmol / L Mn(NO 3 ) 2 ·4H 2 O. Under a water bath at 35 °C and a rotation speed of 1000 r / min, stir and react for 12 h, then centrifuge for solid-liquid separation, collect the white precipitate, wash the white precipitate 6 times with a methanol solution, and freeze-dry at -30 °C and 20 Pa for 24 h to obtain Mn-ZIF-8 powder; The preparation method of the methanol solution of 2-methylimidazole is as follows: Add 2.8 g (0.0341 mol) of 2-methylimidazole to 30 mL of methanol solution, and stir and dissolve at 35 °C for 30 min to obtain it; the preparation method of the methanol solution containing Zn(NO 3 ) 2 ·6H 2 O and Mn(NO 3 ) 2 ·4H 2 O is as follows: Add 3.0 g (0.0101 mol) of Zn(NO 3 ) 2 ·6H 2O and 54 mg (0.215 mmol) of Mn(NO 3 ) 2 ·4H 2 O was added to 270 mL of methanol solution, and stirred and dissolved at 35 °C for 30 min to obtain the solution; (2) First, 1.2 g of the Mn-ZIF-8 powder obtained in step (1) was dispersed in 50 mL of acetic acid solution with a pH value of 2.8, and etched at 40 °C for 4 h, then centrifuged for solid-liquid separation. The precipitate was collected, washed 8 times with methanol solution, centrifuged again to collect the precipitate, and placed in a vacuum drying oven. Vacuum dried at 70 °C and -0.08 MPa for 8 h to obtain a brownish-beige hollow powder; (3) The brownish-beige hollow powder obtained in step (2) was placed in a tubular furnace. Under a high-purity nitrogen atmosphere, it was heated to 1300 °C at a rate of 8 °C / min and carbonized for 3 h, and then cooled to room temperature at a rate of 8 °C / min to obtain a black hollow carbon powder; (4) 500 mg of the black hollow carbon powder obtained in step (3) was dispersed in 20 mL of water, and 30 mL of 0.797 mmol / L Mn(NO 3 ) 2 ·4H 2 O methanol solution was added. Stirred and reacted at 30 °C in a water bath at a rotation speed of 1000 r / min for 8 h, then centrifuged for solid-liquid separation, freeze-dried at -30 °C and 20 Pa for 24 h. Then the obtained powder was placed in a tubular furnace. Under a high-purity nitrogen atmosphere, it was heated to 1300 °C at a rate of 8 °C / min and heat-treated for 4 h, and then cooled to room temperature at a rate of 10 °C / min to obtain a hollow carbon-supported Mn atom catalyst Mn SA / NhC.

[0073] Application Example 2 of a Hollow Carbon-Supported Mn Atom Catalyst The hollow carbon-supported Mn atom catalyst Mn SA / NhC obtained in the method example of the present invention was applied to the air cathode of a zinc-air battery; the specific method was the same as that in Application Example 1.

[0074] In order to evaluate the electrochemical performance of the hollow carbon-supported Mn atom catalyst Mn SA / NhC obtained in the method example of the present invention, it was first prepared into a catalyst ink; the specific method was the same as that in Application Example 1.

[0075] The ORR test method and the LSV curve test method were the same as those in Application Example 1.

[0076] Such as Figure 6 、 7As shown, the hollow carbon-supported Mn atom catalyst Mn SA / NhC obtained by the method example of the present invention has a low charge transfer resistance of 317 Ω and a capacitance of 23.5 mF·cm -2 .

[0077] As Figure 8 , 9 shown, the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Mn atom catalyst Mn SA / NhC obtained by the embodiment of the method of the present invention is 0.813 V (vs RHE), which is better than the half-wave potential (E 1 / 2 ) of the solid carbon-supported Mn atom catalyst Mn SA / NC 0.813 V (vs RHE) obtained in Comparative Example 2, and the Tafel slope is lower, which is 88 mV·dec -1 . Both are far better than the corresponding electrochemical properties of the solid carbon structure Mn SA / NC obtained in Comparative Example 2, and have high ORR activity, indicating that the hollow structure can provide more specific surface area and active sites for metal atoms, and can significantly improve the ORR catalytic activity of the catalyst.

[0078] After testing, the hollow carbon-supported Mn atom catalyst MnSA / NhC obtained by the embodiment of the method of the present invention has high current stability. After running for 8 h, it still has a current retention rate of 90.9%, which is better than the current retention rate of 88.9% of the commercial Pt / C catalyst.

[0079] Example 3 of a hollow carbon-supported Co atom catalyst The hollow carbon-supported Co atom catalyst is formed by anchoring Co atoms on a nitrogen-doped carbon dodecahedron hollow porous cage-like nanostructure; the particle size of the hollow carbon-supported Co atom catalyst is 632.57 ± 28.88 nm, and the carbon shell thickness is 90.13 ± 32.11 nm; the specific surface area of the hollow carbon-supported Co atom catalyst is 1084.6 m 2 ·g -1 , and the specific surface area inside the mesopores is 0.231 cm 3 ·g -1 ·nm -1 ; in the hollow carbon-supported Co atom catalyst, the loading amount of Co atoms is 0.56 wt%, and the mass fraction of nitrogen doping is 5.4 wt%.

[0080] After testing, the hollow carbon-supported Co atom catalyst Co SA / NhC in the embodiment of the present invention is a dodecahedron hollow porous cage-like nanostructure. The catalyst is evenly dispersed, the particle size is 632.57 ± 28.88 nm, the cross-section has a hollow structure, and the carbon shell thickness is 90.13 ± 32.11 nm.

[0081] After detection, the metal particles on the surface of the hollow carbon-supported Co atom catalyst Co SA / NhC in the embodiment of the present invention are uniformly dispersed and loaded in an anchored form, without agglomeration.

[0082] After detection, the specific surface area of the hollow carbon-supported Co atom catalyst Co SA / NhC in the embodiment of the present invention is 1084.6 m 2 ·g -1 , far exceeding the specific surface area of 498.6 m 2 ·g -1 of the solid carbon-supported Co atom catalyst Co SA / NC, indicating that due to its unique structure, the hollow carbon material has a larger specific surface area, and thus more active sites can be used to participate in the catalytic reaction.

[0083] After detection, the specific surface area of the mesopores of the hollow carbon-supported Co atom catalyst Co SA / NhC in the embodiment of the present invention is 0.231 cm 3 ·g -1 ·nm -1 , 0.24 times more than that of Comparative Example 1, indicating that the hollow structure of the hollow carbon material helps to reduce the weight while maintaining a large specific surface area.

[0084] After detection, in the hollow carbon-supported Co atom catalyst Co SA / NhC in the embodiment of the present invention, the loading amount of Co atoms is 0.56 wt%, and the mass fraction of nitrogen doping is 5.4 wt%.

[0085] Example 3 of the preparation method of a hollow carbon-supported Co atom catalyst (1) Rapidly add 30 mL of a methanol solution of 2-nitroimidazole at 0.436 mol / L to 270 mL of a methanol solution containing 17.18 mmol / L Zn(NO 3 ) 2 ·6H 2 O and 0.305 mmol / L Co(NO 3 ) 2 ·6H 2 O within 3 min. Stir and react at 40 °C in a water bath at a rotation speed of 1200 r / min for 12 h, then centrifuge for solid-liquid separation. Collect the white precipitate, wash the white precipitate 6 times with a methanol solution, and freeze-dry at -30 °C and 20 Pa for 24 h to obtain Co-ZIF-8 powder; The preparation method of the methanol solution of 2-nitroimidazole is as follows: Add 1.48 g (0.0131 mol) of 2-nitroimidazole to 30 mL of methanol solution, and stir and dissolve at 35 °C for 30 min to obtain it; the methanol solution containing Zn(NO 3 ) 2 ·6H2 O and Co(NO 3 ) 2 ·6H 2 O was prepared by adding 1.38 g (0.00464 mol) of Zn(NO 3 ) 2 ·6H 2 O and 24 mg (0.0825 mmol) of Co(NO 3 ) 2 ·6H 2 O to 270 mL of methanol solution, and stirring and dissolving at 35 °C for 30 min to obtain the solution; (2) First, disperse 1.36 g of Co-ZIF-8 powder obtained in step (1) in 50 mL of acetic acid solution with a pH value of 2.0, and perform etching at 30 °C for 8 h. Centrifuge for solid-liquid separation, collect the precipitate, wash the precipitate with methanol solution 6 times, centrifuge again to collect the precipitate, place it in a vacuum drying oven, and vacuum dry at 70 °C and -0.08 MPa for 8 h to obtain a brownish-beige hollow powder; (3) Place the brownish-beige hollow powder obtained in step (2) in a tubular furnace, under a high-purity nitrogen atmosphere, heat it to 1200 °C at a rate of 5 °C / min, perform carbonization treatment for 3 h, and then cool it to room temperature at a rate of 5 °C / min to obtain a black hollow carbon powder; (4) Disperse 500 mg of the black hollow carbon powder obtained in step (3) into 20 mL of water, and add 30 mL of 0.305 mmol / L Co(NO 3 ) 2 ·6H 2 O methanol solution, stir and react at 35 °C in a water bath and 1000 r / min for 12 h, then centrifuge for solid-liquid separation, freeze-dry at -30 °C and a vacuum degree of 20 Pa for 24 h. Then place the obtained powder in a tubular furnace, under a high-purity nitrogen atmosphere, heat it to 1000 °C at a rate of 10 °C / min, perform heat treatment for 4 h, and then cool it to room temperature at a rate of 5 °C / min to obtain a hollow carbon-supported Co atom catalyst Co SA / NhC.

[0086] Application Example 3 of a Hollow Carbon-Supported Co Atom Catalyst Apply the hollow carbon-supported Co atom catalyst Co SA / NhC obtained in the method example of the present invention to the air cathode of a zinc-air battery; the specific method is the same as that in Application Example 1.

[0087] In order to evaluate the electrochemical performance of the hollow carbon-supported Co atom catalyst Co SA / NhC obtained in the method example of the present invention, first prepare it into a catalyst ink; the specific method is the same as that in Application Example 1.

[0088] The ORR test method and the LSV curve test method are the same as those in Application Example 1.

[0089] After testing, the hollow carbon-supported Co atom catalyst Co SA / NhC obtained by the method example of the present invention has a low charge transfer resistance of 145 Ω and a capacitance of 46.6 mF·cm -2 .

[0090] After testing, the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Co atom catalyst Co SA / NhC obtained by the embodiment of the method of the present invention is 0.884 V (vs RHE), which is better than the half-wave potential (E 1 / 2 ) of the solid carbon-supported Co atom catalyst CoSA / NC of 0.865 V (vs RHE), and the Tafel slope is low, which is 62 mV·dec -1 . They are all far better than the corresponding electrochemical properties of the solid carbon structure Fe SA / NC obtained in Comparative Example 1, and have high ORR activity, indicating that the hollow structure can provide more specific surface area and active sites for metal atoms, and can significantly improve the ORR catalytic activity of the catalyst.

[0091] After testing, the hollow carbon-supported Co atom catalyst Co SA / NhC obtained by the embodiment of the method of the present invention has high current stability. After running for 8 h, it still has a current retention rate of 91.7%, which is better than the current retention rate of 88.9% of the commercial Pt / C catalyst.

[0092] Example 4 of a hollow carbon-supported Fe and Co atom catalyst The hollow carbon-supported Fe and Co atom catalyst is formed by anchoring Fe and Co atoms on a nitrogen-doped carbon dodecahedron hollow porous cage-like nanostructure; the particle size of the hollow carbon-supported Fe and Co atom catalyst is 554 ± 48.28 nm, and the carbon shell thickness is 86.43 ± 14.12 nm; the specific surface area of the hollow carbon-supported Fe and Co atom catalyst is 1326.1 m 2 ·g -1 , and the specific surface area inside the mesopores is 0.268 cm 3 ·g -1 ·nm -1 ; in the hollow carbon-supported Fe and Co atom catalyst, the loading amounts of Fe and Co atoms are 0.56 wt% and 0.42 wt% respectively, and the mass fraction of nitrogen doping is 7.8 wt%.

[0093] Such as Figure 11As shown in the figure, the hollow carbon-supported Fe and Co atom catalyst FeCo DA / NhC in the embodiment of the present invention is a dodecahedral hollow porous cage-like nanostructure. The catalyst is evenly dispersed with a particle size of 554 ± 48.28 nm. The cross-section has a hollow structure, and the carbon shell thickness is 86.43 ± 14.12 nm.

[0094] After detection, the metal particles on the surface of the hollow carbon-supported Fe and Co atom catalyst FeCo DA / NhC in the embodiment of the present invention are evenly dispersed and loaded in an anchored form without agglomeration.

[0095] After detection, the specific surface area of the hollow carbon-supported Fe and Co atom catalyst FeCo DA / NhC in the embodiment of the present invention is 1326.1 m 2 ·g -1 , far exceeding the specific surface area of the solid carbon-supported Fe and Co atom catalyst FeCo DA / NC, which is 522.3 m 2 ·g -1 . This shows that the hollow dual-atom catalyst inherits the unique hollow structure of the single-atom catalyst, has a larger specific surface area, and has more active sites that can participate in catalytic reactions, greatly improving the structural diversity of the catalyst and providing great convenience for the design and screening of catalysts. At the same time, it exceeds the specific surface area of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in Example 1 of the present invention method, which is 1175.4 m 2 ·g -1 and the specific surface area of the hollow carbon-supported Co atom catalyst Co SA / NhC obtained in Example 3 of the present invention method, which is 1084.6 m 2 ·g -1 . This shows that the dual-atom catalyst can form dual-atom sites through the combination of different metal atoms, greatly improving the structural diversity of the catalyst.

[0096] After detection, the specific surface area of the mesopores in the hollow carbon-supported Fe and Co atom catalyst FeCo DA / NhC in the embodiment of the present invention is 0.268 cm 3 ·g -1 ·nm -1 , which is 0.43 times more than that of Comparative Example 1. This shows that the hollow structure of the hollow carbon material helps to reduce weight while maintaining a large specific surface area.

[0097] After detection, in the hollow carbon-supported Fe and Co atom catalyst FeCo DA / NhC in the embodiment of the present invention, the loading amounts of Fe and Co atoms are 0.56 wt% and 0.42 wt% respectively, and the mass fraction of nitrogen doping is 7.8 wt%.

[0098] Example 4 of the preparation method of a hollow carbon-supported Fe and Co atom catalyst (1) Rapidly add 30 mL of a 2.056 mol / L methanol solution of imidazole into 270 mL of a methanol solution containing 37.35 mmol / L Zn(NO 3 ) 2 ·6H 2 O, 0.996 mmol / L iron acetate, and 0.859 mmol / L Co(NO 3 ) 2 ·6H 2 O within 3 min. Stir and react at 40 °C in a water bath at a rotation speed of 1200 r / min for 12 h, then centrifuge for solid-liquid separation. Collect the white precipitate, wash the white precipitate 6 times with a methanol solution, and freeze-dry at -30 °C and a vacuum degree of 20 Pa for 24 h to obtain FeCo-ZIF-8 powder; The preparation method of the methanol solution of imidazole is as follows: Add 4.2 g (0.0617 mol) of imidazole into 30 mL of methanol solution, and stir and dissolve at 40 °C for 25 min to obtain it; The preparation method of the methanol solution containing Zn(NO 3 ) 2 ·6H 2 O, iron acetate, and Co(NO 3 ) 2 ·6H 2 O is as follows: Add 3.0 g (0.0101 mol) of Zn(NO 3 ) 2 ·6H 2 O, 52.2 mg (0.269 mmol) of iron acetate, and 67.5 mg (0.232 mmol) of Co(NO 3 ) 2 ·6H 2 O into 270 mL of methanol solution, and stir and dissolve at 40 °C for 25 min to obtain it; (2) First, disperse 2.56 g of the FeCo-ZIF-8 powder obtained in step (1) in 50 mL of a formic acid solution with a pH value of 3.0, and etch at 45 °C for 3 h. Centrifuge for solid-liquid separation, collect the precipitate, wash the precipitate 5 times with a methanol solution, centrifuge again to collect the precipitate, and place it in a vacuum drying oven. Vacuum-dry at 70 °C and -0.08 MPa for 8 h to obtain a beige hollow powder; (3) Place the beige hollow powder obtained in step (2) in a tubular furnace. Under a high-purity nitrogen atmosphere, heat it to 1400 °C at a rate of 20 °C / min, carry out carbonization treatment for 3 h, and then cool it to room temperature at a rate of 20 °C / min to obtain black hollow carbon powder; (4) Disperse 500 mg of the black hollow carbon powder obtained in step (3) into 20 mL of water, and add 30 mL of a methanol solution of iron acetate at 0.996 mmol / L and Co(NO 3 ) 2 ·6H 2 O at 0.859 mmol / L. Stir and react at 40 °C in a water bath at a rotation speed of 1200 r / min for 12 h, then centrifuge for solid-liquid separation. Freeze-dry at -30 °C and a vacuum of 20 Pa for 24 h. Then place the obtained powder in a tubular furnace, and under a high-purity nitrogen atmosphere, heat it to 1200 °C at a rate of 20 °C / min for 4 h of heat treatment, and then cool it to room temperature at a rate of 20 °C / min to obtain the hollow carbon-supported Fe and Co atomic catalyst FeCo DA / NhC.

[0099] Application Example 4 of a Hollow Carbon-Supported Fe and Co Atomic Catalyst Apply the hollow carbon-supported Fe and Co atomic catalyst FeCo DA / NhC obtained in the example of the method of the present invention to the air cathode of a zinc-air battery; the specific method is the same as that in Application Example 1.

[0100] In order to evaluate the electrochemical performance of the hollow carbon-supported Fe and Co atomic catalyst FeCo DA / NhC obtained in the example of the method of the present invention, first prepare it into a catalyst ink; the specific method is the same as that in Application Example 1.

[0101] The ORR test method and the LSV curve test method are the same as those in Application Example 1.

[0102] It was detected that the hollow carbon-supported Fe and Co atomic catalyst FeCo DA / NhC obtained in the example of the method of the present invention has a low charge transfer resistance of 108 Ω and a capacitance of 68.4 mF·cm -2 .

[0103] It was detected that the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Fe and Co atomic catalyst FeCo DA / NhC obtained in the example of the method of the present invention is 0.920 V (vs RHE), which is better than the half-wave potential (E 1 / 2 ) of the solid carbon-supported Co atomic catalyst Co SA / NC of 0.865 V (vsRHE), and the Tafel slope is low, being 56 mV·dec -1 , having a high ORR activity, indicating that the hollow structure can provide more specific surface area and active sites for metal atoms, and can significantly improve the ORR catalytic activity of the catalyst; at the same time, it is better than the half-wave potential (E 1 / 2) and the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Co atom catalyst Co SA / NhC 0.884V (vs RHE) obtained in Example 3 of the method of the present invention indicate that the dual-atom catalyst can not only form dual-atom sites through the combination of different metal atoms, greatly improving the structural diversity of the catalyst, but also the synergy between the hollow structure and the dual atoms can further improve the ORR activity of the catalyst.

[0104] After testing, the hollow carbon-supported Fe and Co atom catalyst Fe, Co DA / NhC obtained in the examples of the method of the present invention has high current stability. After running for 8 h, it still has a current retention rate of 93.6%, which is better than the current retention rate of 88.9% of the commercial Pt / C catalyst.

[0105] Example 5 of a hollow carbon-supported Fe and Mn atom catalyst The hollow carbon-supported Fe and Mn atom catalyst is composed of Fe and Mn atoms anchored on a nitrogen-doped carbon dodecahedron hollow cage-like porous nanostructure; the particle size of the hollow carbon-supported Fe and Mn atom catalyst is 568 ± 36.10 nm, and the carbon shell thickness is 85.89 ± 10.12 nm; the specific surface area of the hollow carbon-supported Fe and Mn atom catalyst is 1229.9 m 2 ·g -1 , and the specific surface area inside the mesopores is 0.254 cm 3 ·g -1 ·nm -1 ; in the hollow carbon-supported Fe and Mn atom catalyst, the loading amounts of Fe and Mn atoms are 0.60 wt% and 0.51 wt% respectively, and the mass fraction of nitrogen doping is 8.1 wt%.

[0106] After testing, the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC in the examples of the present invention is a dodecahedron hollow porous cage-like nanostructure. The catalyst is evenly dispersed, with a particle size of 568 ± 36.10 nm, a cross-section having a hollow structure, and a carbon shell thickness of 85.89 ± 10.12 nm.

[0107] After testing, the metal particles on the surface of the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC in the examples of the present invention are evenly dispersed and anchored, without agglomeration.

[0108] As Figure 4 shown, the specific surface area of the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC in the examples of the present invention is 1229.9 m 2 ·g -1, far exceeding the specific surface area of the solid carbon-supported Fe and Mn atomic catalyst FeMn DA / NC obtained in Comparative Example 3 of the present invention, which is 508.2 m 2 ·g -1 , indicating that the hollow dual-atom catalyst inherits the unique hollow structure of the single-atom catalyst, has a larger specific surface area, and has more active sites available for participating in catalytic reactions, greatly improving the structural diversity of the catalyst and providing great convenience for the design and screening of catalysts; at the same time, it exceeds the specific surface area of the hollow carbon-supported Fe atomic catalyst Fe SA / NhC obtained in Example 1 of the method of the present invention, which is 1175.4 m 2 ·g -1 and the specific surface area of the hollow carbon-supported Mn atomic catalyst Mn SA / NhC obtained in Example 2 of the method of the present invention, which is 1150.2 m 2 ·g -1 , indicating that the dual-atom catalyst can form dual-atom sites through the combination of different metal atoms, greatly improving the structural diversity of the catalyst.

[0109] As Figure 5 shown, the specific surface area of the mesopores in the hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC in the example of the present invention is 0.254 cm 3 ·g -1 ·nm -1 , which is 0.36 times more than that of Comparative Example 1, indicating that the hollow structure of the hollow carbon material helps to reduce weight while maintaining a large specific surface area.

[0110] After testing, in the hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC in the example of the present invention, the loadings of Fe and Mn atoms are 0.60 wt% and 0.51 wt% respectively, and the mass fraction of nitrogen doping is 8.1 wt%.

[0111] Example 5 of the preparation method of a hollow carbon-supported Fe and Mn atomic catalyst (1) Rapidly add 30 mL of a methanol solution of 2-nitroimidazole at 1.415 mol / L to 270 mL containing 37.35 mmol / L Zn(NO 3 ) 2 ·6H 2 O, 0.715 mmol / L Fe(NO 3 ) 3 ·9H 2 O and 1.151 mmol / L Mn(NO 3 ) 2 ·4H 2In a methanol solution of O, at 35 °C in a water bath and a rotation speed of 1000 r / min, after stirring and reacting for 12 h, centrifugation is carried out for solid-liquid separation, the white precipitate is collected, the white precipitate is washed 5 times with a methanol solution, and freeze-drying is carried out at -30 °C and a vacuum degree of 20 Pa for 24 h to obtain FeMn-ZIF-8 powder; The preparation method of the methanol solution of the 2-nitroimidazole is as follows: Add 4.8 g (0.0425 mol) of 2-nitroimidazole into 30 mL of methanol solution, and stir and dissolve at 35 °C for 30 min to obtain; the Zn(NO 3 ) 2 ·6H 2 O, Fe(NO 3 ) 3 ·9H 2 O and the preparation method of the methanol solution of Mn(NO 3 ) 2 ·4H 2 O are as follows: Add 3.0 g (0.0101 mol) of Zn(NO 3 ) 2 ·6H 2 O, 78 mg (0.193 mmol) of Fe(NO 3 ) 3 ·9H 2 O, 78 mg (0.311 mmol) of Mn(NO 3 ) 2 ·4H 2 O into 270 mL of methanol solution, and stir and dissolve at 35 °C for 30 min to obtain; (2) First, disperse 3.8 g of the FeMn-ZIF-8 powder obtained in step (1) in 50 mL of tannic acid solution with a pH value of 3.0, and carry out etching at 50 °C for 6 h, centrifugation for solid-liquid separation, collect the precipitate, wash the precipitate 6 times with a methanol solution, centrifuge again to collect the precipitate, place it in a vacuum drying oven, and carry out vacuum drying at 70 °C and -0.08 MPa for 8 h to obtain a brownish-beige hollow powder; (3) Place the brownish-beige hollow powder obtained in step (2) in a tube furnace, under a high-purity nitrogen atmosphere, heat it to 1200 °C at a rate of 35 °C / min, carry out carbonization treatment for 3 h, and then cool it to room temperature at a rate of 25 °C / min to obtain black hollow carbon powder; (4) Disperse 500 mg of the black hollow carbon powder obtained in step (3) in 20 mL of water, add 30 mL of 0.715 mmol / L Fe(NO 3 ) 3 ·9H 2 O and 1.151 mmol / L Mn(NO 3 )2 ·4H 2 A methanol solution of O was stirred and reacted for 12 h at 35 °C in a water bath and at a rotation speed of 1000 r / min. Then, solid-liquid separation was carried out by centrifugation. Freeze-drying was performed for 24 h at -30 °C and a vacuum degree of 20 Pa. Subsequently, the obtained powder was placed in a tubular furnace. Under a high-purity nitrogen atmosphere, it was heated to 1000 °C at a rate of 20 °C / min for heat treatment for 4 h, and then cooled to room temperature at a rate of 20 °C / min to obtain a hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC.

[0112] Application Example 5 of a hollow carbon-supported Fe and Mn atomic catalyst The hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC obtained in the example of the method of the present invention was applied to the air cathode of a zinc-air battery; the specific method was the same as that in Application Example 1.

[0113] To evaluate the electrochemical performance of the hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC obtained in the example of the method of the present invention, it was first prepared into a catalyst ink; the specific method was the same as that in Application Example 1.

[0114] The ORR test method and the LSV curve test method were the same as those in Application Example 1.

[0115] As Figure 6 、 7 shown, the hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC obtained in the example of the method of the present invention has a low charge transfer resistance of 93 Ω and a capacitance of 77.2 mF·cm -2 .

[0116] As Figure 8 、 9 shown, the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Fe and Mn atomic catalyst FeMn DA / NhC obtained in the example of the method of the present invention is 0.922 V (vs RHE), which is far better than the half-wave potential (E 1 / 2 ) of 0.911 V (vs RHE) of the solid carbon-supported Fe and Mn atomic catalyst FeMn DA / NC obtained in Comparative Example 3 of the present invention. Moreover, the Tafel slope is low, being 52 mV·dec -1 , having a high ORR activity, indicating that the hollow structure can provide more specific surface area and active sites for metal atoms, which can significantly improve the ORR catalytic activity of the catalyst; at the same time, it is better than the half-wave potential (E 1 / 2) and the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Mn atom catalyst Mn SA / NhC 0.813 V (vs RHE) obtained in Example 2 of the method of the present invention, indicating that the dual-atom catalyst can not only form dual-atom sites through the combination of different metal atoms, greatly improving the structural diversity of the catalyst, but also the synergy between the hollow structure and the dual atoms can further improve the ORR activity of the catalyst.

[0117] As Figure 10 shown, the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC obtained in the example of the method of the present invention has high current stability. After running for 8 h, it still has a current retention rate of 95.8%, which is better than the current retention rate of 88.9% of the commercial Pt / C catalyst.

[0118] Comparative Example 1 The difference between the comparative example of the present invention and Example 1 of the method is only that: step (2) is removed; black solid carbon powder is obtained in step (3); solid carbon-supported Fe atom catalyst Fe SA / NC is obtained in step (4); the rest is the same as in Example 1 of the method.

[0119] As Figure 12 shown, the solid carbon-supported Fe atom catalyst Fe SA / NC in the comparative example of the present invention is a dodecahedral solid porous cage-like nanostructure. The catalyst has poor dispersibility and agglomeration occurs. The particle size is 425 ± 25.02 nm, which is smaller than the particle size of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in Example 1 of the method of the present invention because the organic acid etching in Example 1 of the method of the present invention changed the surface structure and pore characteristics of the catalyst, resulting in a change in the surface structure of the catalyst, and the external manifestation is a slight increase in the particle size.

[0120] After testing, the metal particles on the surface of the solid carbon-supported Fe atom catalyst Fe SA / NC in the comparative example of the present invention have poor dispersibility and agglomeration occurs.

[0121] After testing, the specific surface area of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention is only 531.7 m 2 ·g -1 .

[0122] After testing, the specific surface area of the mesopores of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention is 0.187 cm 3 ·g -1 ·nm -1 .

[0123] After testing, in the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention, the loading amount of Fe atoms is 0.45 wt%, and the mass fraction of nitrogen doping is 6.0 wt%.

[0124] To evaluate the electrochemical performance of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention, it was first prepared into a catalyst ink; the specific method is the same as that in Application Example 1.

[0125] The ORR test method and the LSV curve test method are the same as those in Application Example 1.

[0126] As Figure 6 、 7 shown, the charge transfer resistance of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention is too high, being 202 Ω, and the capacitance is low, with a capacitance of 36.9 mF·cm -2 .

[0127] As Figure 8 、 9 shown, the half-wave potential (E 1 / 2 ) of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention is 0.872 V (vs. RHE), and the Tafel slope is high, being 68 mV·dec -1 , both being worse than the corresponding electrochemical performance of the hollow carbon structure Fe SA / NhC obtained in Example 1 of the method of the present invention, indicating that acid etching can change the pore structure of the catalyst, thereby possibly affecting the ORR activity of the catalyst.

[0128] After testing, the current stability of the solid carbon-supported Fe atom catalyst Fe SA / NC obtained in the comparative example of the present invention is not good. After running for 8 h, only 88.2% of the current retention rate remains.

[0129] Comparative Example 2 The difference between the comparative example of the present invention and Example 2 of the method is only that: step (2) is removed; black solid carbon powder is obtained in step (3); a solid carbon-supported Mn atom catalyst Mn SA / NC is obtained in step (4); the rest is the same as in Example 2 of the method.

[0130] After testing, the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention is a dodecahedral solid porous cage-like nanostructure. The catalyst has poor dispersibility and agglomeration occurs. The particle size is 441 ± 35.6 nm, which is smaller than that of the hollow carbon-supported Mn atom catalyst Mn SA / NhC obtained in Example 2 of the method of the present invention because the organic acid etching in Example 2 of the method of the present invention changed the surface structure and pore characteristics of the catalyst, resulting in changes in the surface structure of the catalyst, and the external manifestation is a slightly increased particle size.

[0131] After testing, the metal particle dispersion on the surface of the solid carbon-supported Mn atom catalyst Mn SA / NC of the comparative example of the present invention is poor, and agglomeration occurs.

[0132] After testing, the specific surface area of the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention is only 517.3 m 2 ·g -1 .

[0133] After testing, the specific surface area of the mesopores of the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention is 0.176 cm 3 ·g -1 ·nm -1 .

[0134] After testing, in the solid carbon-supported Mn atom catalyst Mn SA / NC of the comparative example of the present invention, the loading amount of Mn atoms is 0.5 wt%, and the mass fraction of nitrogen doping is 6.4 wt%.

[0135] In order to evaluate the electrochemical performance of the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention, it was first prepared into a catalyst ink; the specific method is the same as that in Application Example 1.

[0136] The ORR test method and the LSV curve test method are the same as those in Application Example 1.

[0137] As Figure 6 , 7 shown, the charge transfer resistance of the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention is too high, being 524 Ω, and the capacitance is low, with a capacitance of 19.5 mF·cm -2 .

[0138] As Figure 8 , 9 shown, the half-wave potential (E 1 / 2 ) of the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention is 0.785 V (vs. RHE), and the Tafel slope is high, being 104 mV·dec -1 , both being inferior to the corresponding electrochemical performance of the hollow carbon structure Mn SA / NhC obtained in Example 2 of the method of the present invention, indicating that acid etching can change the pore structure of the catalyst, thereby possibly affecting the ORR activity of the catalyst.

[0139] After testing, the current stability of the solid carbon-supported Mn atom catalyst Mn SA / NC obtained in the comparative example of the present invention is poor, and after running for 8 h, only 85.1% of the current retention rate remains.

[0140] Comparative Example 3 The difference between the comparative example of the present invention and Method Example 5 lies only in: removing step (2); obtaining black solid carbon powder in step (3); obtaining a solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC in step (4); the rest is the same as Method Example 5.

[0141] After testing, the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC of the comparative example of the present invention is a dodecahedral solid porous cage-like nanostructure, with poor catalyst dispersibility, agglomeration occurring, and a particle size of 467 ± 44.2 nm, which is smaller than the particle size of the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC obtained in Method Example 5 of the present invention. This is because the organic acid etching in Method Example 5 of the present invention changed the surface structure and pore characteristics of the catalyst, resulting in a change in the surface structure of the catalyst, and the external manifestation is a slightly increased particle size.

[0142] After testing, the metal particles on the surface of the solid carbon-supported Mn atom catalyst Mn SA / NC of the comparative example of the present invention have poor dispersibility and agglomeration occurs.

[0143] As Figure 4 shown, the specific surface area of the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC obtained in the comparative example of the present invention is only 508.2 m 2 ·g -1 .

[0144] As Figure 5 shown, the specific surface area of the mesopores of the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC obtained in the comparative example of the present invention is 0.172 cm 3 ·g -1 ·nm -1 .

[0145] After testing, in the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NhC of the comparative example of the present invention, the loadings of Fe and Mn atoms are 0.58 wt% and 0.49 wt% respectively, and the mass fraction of nitrogen doping is 7.6 wt%.

[0146] In order to evaluate the electrochemical performance of the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC obtained in the comparative example of the present invention, it was first prepared into a catalyst ink; the specific method is the same as in Application Example 1.

[0147] The ORR test method and the LSV curve test method are the same as in Application Example 1.

[0148] As Figure 6 , 7As shown, the charge transfer resistance of the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC obtained in the comparative example of the present invention is too high, being 157 Ω, and the capacitance is low, being 46.7 mF·cm -2 .

[0149] As Figure 8 , 9 shown, the half-wave potential (E 1 / 2 ) of the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC obtained in the comparative example of the present invention is 0.911 V (vs RHE), lower than the half-wave potential (E 1 / 2 ) of the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC obtained in Example 5 of the method of the present invention, which is 0.922 V (vs RHE), and the Tafel slope is high, being 59 mV·dec -1 , both are inferior to the corresponding electrochemical performance of the hollow carbon structure-supported Fe and Mn atom catalyst FeMn DA / NhC obtained in Example 5 of the method of the present invention. This is because the acid etching process generates micropores, changing the pore structure of the catalyst, thereby changing the local electronic structure of the active sites in the single-atom catalyst, thus affecting the change in the ORR activity of the catalyst.

[0150] After detection, the current stability of the solid carbon-supported Fe and Mn atom catalyst FeMn DA / NC obtained in the comparative example of the method of the present invention is only 90.2% current retention rate after running for 8 h, lower than the 95.8% current stability of the hollow carbon-supported Fe and Mn atom catalyst FeMn DA / NhC obtained in Example 5 of the method of the present invention. This is because the acid etching process in Example 5 of the method of the present invention has a favorable impact on the electronic structure, surface structure and metal-support interaction of the catalyst.

[0151] Comparative Example 4 The difference between the comparative example of the present invention and Example 1 of the method is only that: step (4) is removed; the hollow carbon-supported Fe atom catalyst Fe SA / NhC is obtained in step (3); the rest is the same as in Example 1 of the method.

[0152] After detection, the hollow carbon-supported Fe atom catalyst Fe SA / NhC in the comparative example of the present invention is a dodecahedral hollow porous cage-like nanostructure, the catalyst dispersion is poor, agglomeration occurs, and the particle size is 503.1 ± 33.02 nm, smaller and more uneven than the particle size of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained in Example 1 of the method of the present invention. This is because the first pyrolysis process forms a thermodynamically stable phase, ensuring the structure of the hollow carbon-supported Fe atom catalyst Fe SA / NhC, but due to the lack of the second pyrolysis process, the electronic properties of the metal atoms do not undergo a secondary change, and the dispersed state of the metal atoms on the support cannot be ensured.

[0153] After testing, the metal particle dispersion on the surface of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC of the comparative example of the present invention is poor, agglomeration occurs, and the metal particle adsorption is poor.

[0154] After testing, the specific surface area of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained from the comparative example of the present invention is only 980.4 cm 3 ·g -1 。

[0155] After testing, the specific surface area of the mesopores of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained from the comparative example of the present invention is 0.205 cm 3 ·g -1 ·nm -1 。

[0156] After testing, in the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained from the comparative example of the present invention, the loading amount of Fe atoms is 0.47 wt%, and the mass fraction of nitrogen doping is 5.8 wt%.

[0157] In order to evaluate the electrochemical performance of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained from the comparative example of the present invention, it was first prepared into a catalyst ink; the specific method is the same as that in Application Example 1.

[0158] The ORR test method and the LSV curve test method are the same as those in Application Example 1.

[0159] After testing, the charge transfer resistance of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained from the comparative example of the present invention is too high, being 180 Ω, and the capacitance is low, being 45.8 mF·cm -2 。

[0160] After testing, the half-wave potential (E 1 / 2 ) of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained from the comparative example of the present invention is 0.888 V (vs RHE), lower than the half-wave potential (E 1 / 2 ) of 0.899 V (vs RHE) of the Fe atom-loaded hollow carbon catalyst Fe SA / NhC obtained in Example 1 of the method of the present invention, and the Tafel slope is high, being 62 mV·dec -1 , both are worse than the corresponding electrochemical performance of the Fe atom-loaded hollow carbon structure catalyst Fe SA / NhC obtained in Example 1 of the method of the present invention, indicating that the secondary heat treatment can control the dispersion state of metal atoms on the carrier and prevent them from aggregating to form clusters or nanoparticles at high temperatures.

[0161] After testing, the current stability of the hollow carbon-supported Fe atom catalyst Fe SA / NhC obtained from the comparative example of the present invention is poor. After running for 8 hours, only 91.2% of the stability remains.

Claims

1. A hollow carbon-supported metal atom catalyst, characterized in that: It is composed of one or several metal atoms anchored in a nitrogen-doped carbon polyhedron hollow porous cage-like nanostructure.

2. The hollow carbon supported metal atom catalyst according to claim 1, characterized in that: The particle size of the hollow carbon-supported metal atom catalyst is 360-700 nm, the carbon shell thickness is 18-100 nm; the specific surface area of ​​the hollow carbon-supported metal atom catalyst is 1000-1400 m 2 ·g -1 The specific surface area of ​​the mesopores is 0.1 to 0.4 cm 3 ·g -1 ·nm -1 ; In the hollow carbon-loaded metal atom catalyst, the total loading of metal atoms is 0.5 to 25 wt%, and the mass fraction of nitrogen doping is 5 to 10 wt%; the metal atoms include one or more of iron, nickel, cobalt, tin, manganese, copper, cerium, molybdenum, vanadium or ruthenium.

3. A method for preparing the hollow carbon supported metal atom catalyst as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) quickly adding an alcohol solution of an imidazole organic ligand to an alcohol solution containing zinc salt and other metal salts, stirring for reaction, centrifuging, washing the precipitate, and freeze-drying to obtain metal-ZIF-8 powder; (2) dispersing the metal-ZIF-8 powder obtained in step (1) in an organic acid solution, etching, centrifuging, washing the precipitate, centrifuging, and vacuum drying to obtain a brown-beige hollow powder; (3) subjecting the brown-beige hollow powder obtained in step (2) to carbonization treatment under an inert atmosphere, and then cooling to room temperature to obtain black hollow carbon powder; (4) The black hollow carbon powder obtained in step (3) is dispersed in water, and an alcohol solution containing the same other metal salt as in step (1) is added again. After stirring for reaction, the mixture is centrifuged, freeze-dried, heat-treated under an inert atmosphere, and cooled to room temperature to obtain a hollow carbon-supported metal atom catalyst.

4. The method for preparing the hollow carbon-supported metal atom catalyst according to claim 3, characterized in that: In step (1), the volume ratio of the alcohol solution of the imidazole organic ligand to the alcohol solution containing zinc salt and other metal salts is 1:6-12; the concentration of N element in the alcohol solution of the imidazole organic ligand is 1-10 mol / L; the rapid addition refers to adding within 1-3 min; in the alcohol solution containing zinc salt and other metal salts, the concentration of zinc ions in the zinc salt is 3-100 mmol / L, and the molar ratio of metal ions in other metal salts to zinc ions in the zinc salt is 0.005-0.4:1; the stirring reaction refers to: stirring for 10-60 h at a speed of 800-1400 r / min in a water bath at room temperature to 50°C; washing with methanol and / or ethanol, or their aqueous solutions for 2-15 times; the freeze-drying temperature is -30--55°C, the vacuum degree is 10-30 Pa, and the time is 12-60 h.

5. The method for preparing the hollow carbon-supported metal atom catalyst according to claim 3 or 4, characterized in that: In step (1), the preparation method of the alcohol solution of the imidazole organic ligand is: adding the imidazole organic ligand to the alcohol solution, stirring and dissolving to obtain the solution; the imidazole organic ligand includes one or more of imidazole, 2-methylimidazole or 2-nitroimidazole; the preparation method of the alcohol solution containing zinc salt and other metal salts is: adding zinc salt and other metal salts to the alcohol solution, stirring and dissolving to obtain the solution; the zinc salt includes Zn(NO3)2·6H2O; the other metal salts include one or more of iron salts, nickel salts, cobalt salts, tin salts, manganese salts, copper salts, cerium salts, molybdenum salts, vanadium salts or ruthenium salts, and hydrates thereof; the alcohol solution is methanol and / or ethanol, or an aqueous solution thereof; the stirring and dissolving temperature is room temperature to 50°C, and the time is 20 to 60 minutes.

6. The method for preparing the hollow carbon supported metal atom catalyst according to any one of claims 3 to 5, characterized in that: In step (2), the mass volume ratio of the metal-ZIF-8 powder to the organic acid solution is 5 to 100 g / L; the etching temperature is room temperature to 60°C, and the time is 3 to 72 hours; the pH value of the organic acid solution is 2.0 to 3.5; the organic acid solution includes one or more of tannic acid, formic acid, acetic acid, propionic acid, butyric acid, difluoroacetic acid, trifluoroacetic acid, isobutyric acid or 2-methylbutyric acid; washing with methanol and / or ethanol, or their aqueous solutions for 3 to 12 times; the vacuum drying temperature is 60 to 100°C, the vacuum degree is -0.01 to -0.10 MPa, and the time is 4 to 36 hours.

7. The method for preparing the hollow carbon supported metal atom catalyst according to any one of claims 3 to 6, characterized in that: In step (3), the carbonization treatment refers to: heating to 600-1500°C at a rate of 1-40°C / min, carbonizing for 1-24h; and cooling to room temperature at a rate of 1-30°C / min.

8. The method for preparing the hollow carbon supported metal atom catalyst according to any one of claims 3 to 7, characterized in that: In step (4), the concentration of the hollow carbon powder dispersed in water is 20-30 mg / mL; the volume ratio of the water to the alcohol solution is 1:1-3; the total concentration of metal ions in the alcohol solution is 0.2-8.0 mmol / L; the temperature of the stirring reaction is room temperature-50°C, the rotation speed is 500-1200 r / min, and the stirring time is 3-24 h; the freeze-drying temperature is -30--55°C, the vacuum degree is 10-30 Pa, and the time is 6-72 h; the heat treatment refers to: heating to 800-1600°C at a rate of 1-50°C / min, heat treatment for 2-6 h; cooling to room temperature at a rate of 1-30°C / min; in steps (3) and (4), the inert atmosphere includes one or more of nitrogen, argon or helium.

9. An application of the hollow carbon supported metal atom catalyst as claimed in claim 1 or 2, characterized in that: The hollow carbon-supported metal atom catalyst according to claim 1 or 2 is applied to the cathode of an energy storage battery and a conversion battery; the energy storage battery includes a metal-air battery, a metal ion battery or a supercapacitor; the conversion battery includes a microbial fuel cell.

Citation Information

Patent Citations

  • Nitrogen / metal atom doped hollow polyhedral nanocarbon shell material and preparation method

    CN107459029A

  • Preparation method of metal monatomic site carbon composite material with hollow structure

    CN111924820A

  • Double-thin-layer polyphthalocyanine-loaded hollow nanocarbon spherical shell electrocatalyst as well as preparation method and application thereof

    CN116960373A